Composite material as well as preparation method and application thereof
By using manganese-tin bimetallic composite materials to support iridium or iridium oxide, the problem of excessive oxygen adsorption capacity of IrO2 catalysts is solved, and the effect of reducing the amount of iridium and improving the activity and stability of the catalyst is achieved, which promotes the efficiency of water electrolytics and Increased costs.
Patent Information
- Application Number
- CN202411518582.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
AI Technical Summary
The existing IrO2 catalyst has too strong oxygen adsorption capacity during water electrolysis, which makes it difficult for the reaction intermediate to further react and the oxygen generated on the catalyst surface difficult to release, limiting the efficiency and cost of water electrolysis.
A composite material supported by manganese and tin bimetallic materials is used to regulate the electronic structure and oxygen adsorption energy of the catalyst through doping of manganese and tin support, reduce the amount of iridium used and improve the activity and stability of the catalyst.
It effectively reduces the amount of iridium used in the catalyst, improves the activity and stability of the OER reaction, reduces the cost of water electrolysis, and expands the application prospects of renewable energy.
Smart Images

Figure CN119465235A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of energy catalysis technology, and in particular relates to a composite material and a preparation method and application thereof. Background Art
[0002] In proton exchange membrane water electrolysis (PEMWE), anodic redox catalysts (Oxygen Evolution Reaction, OER) play a crucial role in water electrolysis and other energy conversion processes because they can promote the electrochemical decomposition of oxygen.
[0003] At present, the OER catalyst of commercial PEMWE is still IrO2, but its high price limits the large-scale industrial application of PEMWE. In addition, IrO2 has a strong oxygen adsorption capacity, which is not conducive to the further reaction of reaction intermediates and the release of oxygen generated on the catalyst surface. Therefore, the design and preparation of acidic OER catalysts with low iridium content, high activity and high stability are of great significance for improving energy conversion efficiency, reducing energy conversion costs and promoting the application of renewable energy. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a composite material and a preparation method and application thereof to solve the technical problem that the existing IrO2 has too strong oxygen adsorption capacity, which is not conducive to further reaction of the reaction intermediates.
[0005] In a first aspect, an embodiment of the present application provides a composite material, comprising a carrier composed of a metal compound doped with a metal and an iridium element or iridium oxide loaded on the surface of the carrier;
[0006] The metal is selected from at least one of manganese and tin;
[0007] The metal compound is selected from at least one of manganese dioxide, tin oxide, stannous hydroxide and tin hydroxide.
[0008] In some embodiments, the molar ratio of manganese element to tin element in the carrier is 1:(0.1-5).
[0009] In a second aspect, the present invention provides a method for preparing a composite material, comprising the following steps:
[0010] Provide manganese precursor, tin precursor, reaction additives, iridium source and solvent;
[0011] Mixing the manganese precursor, the tin precursor and the reaction additive, and reacting to obtain a carrier;
[0012] The carrier, the iridium source and the solvent are mixed and reacted to obtain the composite material.
[0013] In some embodiments, the mass ratio of the carrier to the iridium source is 1:(0.25-4).
[0014] In some embodiments, the manganese precursor includes at least one of manganese acetate, manganese chloride, and potassium permanganate.
[0015] In some embodiments, the tin precursor includes at least one of tin chloride, stannous chloride, and sodium stannate.
[0016] In some embodiments, the reaction additive includes at least one of hydrochloric acid, sulfuric acid, nitric acid, ammonia water and ethylenediamine.
[0017] In some embodiments, the iridium source includes at least one of iridium trichloride and chloroiridic acid.
[0018] In some embodiments, the reagent includes at least one of water, ethanol, n-propanol, and isopropanol.
[0019] In some embodiments, the manganese precursor, the tin precursor and the reaction additive are mixed and reacted to obtain a carrier, comprising:
[0020] At 100°C to 200°C, react for 6h to 18h and then cool to room temperature;
[0021] The carrier is washed and vacuum dried at 40°C to 60°C to obtain the carrier.
[0022] In some embodiments, the step of mixing the carrier, the iridium source, and the solvent to obtain the composite material comprises:
[0023] At 100°C to 200°C, react for 6h to 18h and then cool to room temperature;
[0024] The composite material is washed and vacuum dried at 40° C. to 60° C. to obtain the composite material.
[0025] In a third aspect, an embodiment of the present application provides a catalyst, comprising the composite material described in the first aspect or the composite material prepared by the preparation method described in the second aspect.
[0026] In a fourth aspect, the present application provides a proton exchange membrane water electrolysis reaction, using the catalyst described in the third aspect as an anode oxygen evolution catalyst.
[0027] In some embodiments, the method for preparing the anode comprises the following steps:
[0028] Dispersing the catalyst in the dispersion, mixing and pre-treating to obtain a slurry;
[0029] Spraying the slurry onto polytetrafluoroethylene to form the anode hydrogen evolution catalyst;
[0030] Then, the anode hydrogen evolution catalyst is transferred to a proton exchange membrane to obtain the anode.
[0031] The composite material provided in the embodiment of the present application, its preparation method and application, through the iridium or iridium oxide loaded by manganese and tin bimetallic materials, on the one hand, the manganese tin carrier loading can effectively reduce the use of iridium metal or iridium oxide in the catalyst, because iridium metal and iridium oxide have high costs, so that the cost can be effectively reduced, and the atomic utilization efficiency of iridium can be improved; on the other hand, manganese dioxide has good stability in acidic systems. However, manganese dioxide has poor conductivity, and after being doped with tin (because the electronegativity of tin metal is higher than one level, its outer electronic structure is similar to carbon), the conductivity can be effectively improved. Specifically, tin doping can improve the conductivity of the carrier, optimize the electronic structure of the catalyst (composite material), and keep iridium in a lower chemical state, improve the antioxidant capacity of iridium, thereby enhancing the stability of the catalyst in the OER reaction; and adjust the oxygen adsorption energy of the iridium-based catalyst so that the oxygen adsorption energy on the catalyst surface is moderate, thereby improving the OER activity and stability.
[0032] In addition, the preparation method provided in the embodiment of the present application has a simple preparation process, low cost, easy regulation, and is suitable for batch preparation. The obtained composite material has a low overpotential for the acidic oxygen evolution reaction when used as a catalyst (especially as a catalyst in OER), and has high catalyst activity, and has broad application prospects in the field of acidic water electrolysis oxygen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 is the XRD diagram of the carrier in the composite material provided in the first embodiment of the present application;
[0035] Figure 2 is a SEM image of the carrier in the composite material provided in the first embodiment of the present application;
[0036] Figure 3 is the XRD diagram of the carrier in the composite material provided in the second embodiment of the present application;
[0037] Figure 4is a SEM image of the carrier in the composite material provided in the second embodiment of the present application;
[0038] Figure 5 is an XRD diagram of the carrier in the composite material provided in the third embodiment of the present application;
[0039] Figure 6 is a SEM image of the carrier in the composite material provided in the third embodiment of the present application;
[0040] Figure 7 is a TEM image of commercial iridium oxide provided in Comparative Example 1;
[0041] Figure 8 is a particle size distribution diagram of commercial iridium oxide provided in Comparative Example 1;
[0042] Fig. 9 is the XRD pattern of the carrier provided in Comparative Example 2;
[0043] Fig.10 This is the XRD diagram of the carrier provided in Comparative Example 3. DETAILED DESCRIPTION
[0044] In the following description, specific details such as specific system structures, technologies, etc. are proposed for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present application. However, it should be clear to those skilled in the art that the embodiments of the present application can also be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from hindering the description of the embodiments of the present application.
[0045] It should also be understood that the term “and / or” used in the description of the embodiments of the present application and the appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0046] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0047] It should be understood that the orientation or position relationship indicated by terms such as "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0048] In addition, in the description of the embodiments of the present application and the appended claims, the terms "first", "second", "third", etc. are only used to distinguish the descriptions and cannot be understood as indicating or implying relative importance.
[0049] References to "some embodiments" or "some embodiments" etc. described in the specification of the embodiments of the present application mean that one or more embodiments of the embodiments of the present application include specific features, structures or characteristics described in conjunction with the embodiment. Thus, the statements "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear in the different parts of this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways. "Multiple" refers to two or more.
[0050] In PEMWE, OER plays a crucial role in water electrolysis and other energy conversion processes as they can promote the electrochemical decomposition of oxygen.
[0051] First, the design of OER catalysts can be achieved by controlling their surface structure, composition, and morphology. Rationally designed catalysts can provide more active sites, regulate the reaction process, and increase the reaction rate and catalytic stability. These properties can help improve the electrocatalytic performance of the catalyst and achieve more efficient redox reactions.
[0052] Secondly, the preparation of efficient OER catalysts requires the selection of appropriate materials and synthesis methods. High-quality catalyst materials have excellent conductivity, chemical stability, surface activity and reaction characteristics, which directly affect the performance of the catalyst. The synthesis method and process conditions during the preparation process will also affect the structure and performance of the catalyst, so precise control is required to obtain the ideal catalytic effect.
[0053] In general, the design and preparation of efficient OER catalysts is of great significance for promoting the development of hydrogen energy and other clean energy. By continuously optimizing the design and preparation process of catalysts, we can improve energy conversion efficiency, reduce energy conversion costs, achieve sustainable utilization of clean energy, and better meet society's demand for clean energy.
[0054] At present, the OER catalyst of commercial PEMWE is still IrO2, but its high price limits the large-scale industrial application of PEMWE. Therefore, the design and preparation of acidic OER catalysts with low iridium content, high activity and high stability are of great significance for improving energy conversion efficiency, reducing energy conversion costs and promoting the application of renewable energy.
[0055] In view of this, the present invention provides a composite material and a preparation method and application thereof, wherein the composite material is a Mn-Sn bimetallic carrier loaded with metal iridium or iridium oxide, and the interaction between the metal compound carrier doped with metal and the metal iridium or iridium oxide can reduce the iridium loading and adjust the electronic structure of the catalyst. In addition, the oxygen adsorption capacity of IrO2 is too strong, which is not conducive to the further reaction of the reaction intermediates and the release of O2 generated on the catalyst surface, while the Mn-Sn bimetallic carrier can reduce the oxygen adsorption energy on the catalyst surface. Therefore, the Mn-Sn bimetallic carrier helps to reduce the iridium loading, thereby improving the OER activity and stability.
[0056] The embodiment of the present application provides a composite material, including a carrier composed of a metal compound doped with a metal and an iridium element or iridium oxide loaded on the surface of the carrier;
[0057] The metal is selected from at least one of manganese and tin;
[0058] The metal compound is at least one selected from manganese dioxide, tin oxide, stannous hydroxide and tin hydroxide.
[0059] The composite material provided in the embodiment of the present application, through the loading of iridium element or iridium oxide by manganese-tin bimetallic carrier, effectively reduces the usage of precious metal iridium on the first aspect: iridium is a rare and expensive precious metal, widely used in OER catalysts in PEM (proton exchange membrane) electrolyzers. However, the high cost of iridium limits the large-scale application of PEM water electrolysis technology. By using manganese-tin bimetallic carriers, the loading of iridium can be significantly reduced. As a carrier material, manganese-tin bimetallic can significantly reduce the loading of iridium while maintaining or even improving catalytic activity due to its high conductivity, acid stability and large specific surface area. The second aspect improves the electronic structure of the composite material: manganese and tin, as carrier materials, have good electrochemical stability and adjustable electronic properties. These elements can form strong electronic interactions with iridium or iridium oxide, thereby optimizing the electronic structure of the catalyst. Specifically, this interaction can reduce the oxygen adsorption energy on the iridium surface and improve the catalytic efficiency of OER. By loading Ir or IrO2 nanoparticles on the surface of a manganese-tin bimetallic carrier, a heterojunction can be formed. The work function difference drives electrons to flow from the conduction band of the carrier to IrO2, so that the antibonding orbit of IrO2 is more fully filled with electrons, thereby weakening the adsorption energy of oxygen intermediates and improving the intrinsic activity of oxygen evolution. Third, improve the conductivity of the composite material: the addition of manganese and tin can not only adjust the electronic structure of the composite material, but also significantly improve its conductivity. This is particularly important for OER catalysts, because high conductivity helps to improve the charge transfer efficiency, thereby improving the catalytic activity. Fourth, enhance the stability of the catalyst: long-term operation stability is a key performance indicator of the catalyst in practical applications. By using a manganese-tin bimetallic carrier, the structural stability and durability of the catalyst can be improved.
[0060] In some embodiments, the doped metal is tin and the metal compound is manganese dioxide. Alternatively, the doped metal may also be manganese and the metal compound may be stannous hydroxide and tin hydroxide. In the application, the carrier includes Mn X Sn 1-X O2, wherein 0<X<1. In a specific embodiment, the carrier includes Mn 0.86 Sn 0.14 O2、Mn 0.82 Sn 0.18 O2、Mn 0.125 Sn 0.875O2. In other embodiments, the carrier also includes MnSn(OH)6. The above-mentioned carrier uses manganese-tin bimetal as a carrier. Manganese and tin, two elements, have good electrochemical stability and adjustable electronic properties. As carriers, they can effectively affect the electronic environment of iridium or iridium oxide, thereby optimizing the surface properties of the catalyst. By reducing the oxygen adsorption energy, the decomposition process of water molecules can be more effectively promoted, thereby improving the overall efficiency of OER. In addition, the design of this composite material also helps to enhance the stability of the catalyst, which is particularly important for long-term applications such as electrolysis of water to produce hydrogen.
[0061] In some embodiments, the molar ratio of manganese to tin in the carrier is 1:(0.1-5). In some optional embodiments, the molar ratio of manganese to tin in the carrier can be any ratio within the range of 1:(0.1-5), such as 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 0.82:0.18 and 0.86:0.14. In this way, by adjusting different manganese-tin ratios, the appropriate ratio can optimize the electronic environment of iridium or iridium oxide, thereby improving the catalytic activity. A suitable manganese-tin ratio can enhance the electron transfer between metallic iridium and the carrier, reduce the oxygen adsorption energy on the iridium surface, and improve the catalytic efficiency of OER. A suitable manganese-tin ratio can improve the conductivity of the composite material. High conductivity helps to improve the charge transfer efficiency, thereby enhancing the catalytic activity. By adjusting the manganese-tin ratio, an optimal value can be found so that the oxygen adsorption energy on the catalyst surface is the lowest. This helps to more effectively promote the decomposition of water molecules and improve the overall efficiency of OER. The appropriate manganese-tin ratio can increase the effective active sites on the catalyst surface, thereby improving the catalytic activity. Different ratios of manganese-tin carriers can provide different structural stabilities. A higher tin content can enhance the corrosion resistance and mechanical strength of the carrier and prevent the catalyst from degrading during long-term operation. The appropriate manganese-tin ratio can prevent the aggregation of iridium nanoparticles, thereby maintaining the dispersion and stability of the catalyst. By optimizing the manganese-tin ratio, a ratio can be found that can maintain high catalytic activity while significantly reducing the iridium loading. This helps to reduce the overall cost of the catalyst. Low-cost, high-performance catalysts can improve the economic benefits of the entire water electrolysis system and promote its large-scale application. Different manganese-tin ratios affect the specific surface area of the composite material. A high specific surface area can provide more active sites and improve the catalytic efficiency. Changes in the manganese-tin ratio can also affect the pore structure of the composite material, optimize the mass transfer process, and improve the catalytic activity.
[0062] The present invention provides a method for preparing a composite material, comprising the following steps:
[0063] S10, providing a manganese precursor, a tin precursor, a reaction additive, an iridium source and a solvent;
[0064] S20, mixing a manganese precursor, a tin precursor and a reaction additive, and reacting to obtain a carrier;
[0065] S30, mixing the carrier, the iridium source and the solvent, and reacting to obtain a composite material.
[0066] The preparation method provided in the embodiment of the present application has simple process, low cost, easy control, and is suitable for batch preparation. The obtained composite material can be used as a catalyst, has a low overpotential for the acidic oxygen evolution reaction, has high catalyst activity, and has broad application prospects in the field of acidic water electrolysis oxygen evolution.
[0067] In step S10, the manganese precursor includes but is not limited to at least one of manganese acetate, manganese chloride, potassium permanganate, etc. The tin precursor includes but is not limited to at least one of tin chloride, stannous chloride, sodium stannate, etc. The reaction additive includes but is not limited to at least one of hydrochloric acid, sulfuric acid, nitric acid, ammonia water, ethylenediamine, etc. Manganese acetate has high solubility, is easy to control the reaction conditions, and the manganese compound formed has high purity. Manganese chloride is cheap, has high solubility, and has good reaction activity. Potassium permanganate has strong oxidizing properties and can be used to prepare manganese compounds with high oxidation states. It is mainly used in synthesis processes that require high oxidation states of manganese, such as the preparation of manganese dioxide. Tin chloride has high solubility and good reaction activity, and is suitable for the preparation of high-purity tin compounds. Stannous chloride has strong reducing properties and can be used to prepare low-valent tin compounds. It is suitable for synthesis processes that require low-valent tin, such as the preparation of tin oxides, etc. Sodium stannate has good water solubility and mild reaction conditions. Hydrochloric acid is strongly acidic and can adjust the pH value of the solution to promote certain reactions. Sulfuric acid is not easy to volatilize and is suitable for high-temperature reactions. Nitric acid has strong oxidizing properties and can be used to remove organic impurities and improve product purity. Ammonia is weakly alkaline and can adjust the pH value of the solution and promote certain precipitation reactions. Ethylenediamine has strong coordination ability and can form stable complexes with metal ions.
[0068] In step S10, the iridium source includes at least one of iridium trichloride and chloroiridic acid. The reagent includes at least one of ethanol, n-propanol and isopropanol. Iridium trichloride has high solubility, good reaction activity, and is easy to prepare uniformly dispersed iridium nanoparticles. It is used for preparing iridium-based composite materials by solution method, such as sol-gel method, hydrothermal method, etc. Chloroiridic acid has high solubility and good stability, and can provide high concentration of iridium ions. It is suitable for synthesis processes requiring high concentration of iridium ions, such as coprecipitation method, impregnation method, etc. Ethanol has high solubility, moderate volatility, and is easy to control reaction conditions. It is commonly used in sol-gel method, impregnation method, etc., and can be used as a solvent or dispersant to help uniformly disperse the iridium source and carrier material. N-propanol has high solubility and low volatility, and is suitable for reactions requiring a slower evaporation rate. It is suitable for synthesis methods requiring a longer reaction time, such as solvent thermal method, hydrothermal method, etc. Isopropanol has high solubility, moderate volatility, and has certain antioxidant properties. It is often used to prepare high-purity nanoparticles and can be used as a solvent or dispersant to prevent the agglomeration of nanoparticles.
[0069] In step S20, a manganese precursor, a tin precursor and a reaction additive are mixed and reacted to obtain a carrier, including:
[0070] S21, mixing the manganese precursor, the tin precursor and the reaction additive uniformly;
[0071] S22, transferring the uniformly mixed solution to a polytetrafluoroethylene-lined high-pressure reactor, reacting at 100° C. to 200° C. for 6 h to 18 h, and naturally cooling to room temperature;
[0072] S23, washing with water and ethanol for multiple times, and vacuum drying at 40°C to 60°C to obtain the carrier.
[0073] In step S21, the combination of manganese precursor, tin precursor and reaction additive includes potassium permanganate, tin chloride, hydrochloric acid; manganese acetate, tin chloride, ammonia water; manganese acetate, tin chloride, ethylenediamine; manganese acetate, sodium stannate, ammonia water; manganese acetate, sodium stannate, ethylenediamine, etc.
[0074] In step S22, the reaction temperature may be any value within the range of 100° C. to 200° C., such as 100° C., 120° C., 140° C., 150° C., 160° C., 180° C., 200° C. The reaction time may be any value within the range of 6 h to 18 h, such as 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, etc.
[0075] In step S23, the reaction product is washed with deionized water and ethanol for multiple times to remove residual reaction additives and other impurities. The washed product is dried at a certain temperature, for example, in a vacuum drying oven at 60°C to 80°C for more than 12 hours to ensure complete drying. The vacuum drying temperature can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc., any value within the range of 60°C to 80°C.
[0076] In step S30, the carrier, the iridium source and the solvent are mixed and reacted to obtain a composite material, which includes:
[0077] S31, the carrier, the iridium source and the solvent are uniformly mixed by stirring;
[0078] S32, transferring the uniformly mixed solution to a polytetrafluoroethylene-lined high-pressure reactor, reacting at 100° C. to 200° C. for 6 h to 18 h, and naturally cooling to room temperature;
[0079] S33, washing with water and ethanol for multiple times, and vacuum drying at 40° C. to 60° C. to obtain a composite material.
[0080] In step S31, the mass ratio of the carrier to the iridium source is 1:(0.25-4). In some optional embodiments, the mass ratio of the carrier to the iridium source can be any ratio within the range of 1:(0.25-4), such as 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, etc. By adjusting the mass ratio of the carrier to the iridium source, the iridium loading can be effectively reduced, thereby significantly reducing the cost of the catalyst. Iridium is a rare and expensive precious metal, and reducing its usage is crucial to achieving large-scale applications. Different mass ratios affect the dispersibility and electronic structure of iridium on the carrier, thereby affecting the catalytic activity. The appropriate ratio can make the iridium nanoparticles evenly dispersed on the carrier and improve the catalytic activity. The mass ratio of the carrier can affect the structural stability and durability of the catalyst. The appropriate ratio can prevent the aggregation and shedding of iridium nanoparticles and improve the long-term stability of the catalyst.
[0081] In step S32, the carrier includes Mn 0.86 Sn 0.14 O2, MnSn (OH) 6, and the iridium source includes any one of Ir and IrO2. The reaction temperature can be 100 ° C, 120 ° C, 140 ° C, 150 ° C, 160 ° C, 180 ° C, 200 ° C, etc., any value in the range of 100 ° C to 200 ° C. The reaction time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, etc., any value in the range of 6h to 18h.
[0082] In step S33, the obtained composite material includes IrO2-Mn 0.82 Sn 0.18 O2, Ir-MnSn(OH)6. The reaction product is washed with deionized water and ethanol several times to remove residual reagents and other impurities. The washed product is dried at a certain temperature, for example, in a vacuum drying oven at 60°C to 80°C for more than 12 hours to ensure complete drying. The vacuum drying temperature can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc., any value within the range of 60°C to 80°C.
[0083] An embodiment of the present application also provides an application of a composite material, that is, the composite material provided in the first aspect or the composite material prepared by the method provided in the second aspect is used as a catalyst.
[0084] The embodiment of the present application also provides an application, in which the catalyst described in the third aspect is used as an anode hydrogen evolution catalyst in the proton exchange membrane water electrolysis reaction. In this way, the Ir loading can be reduced and the electronic structure of the catalyst can be adjusted by the interaction between the Mn-Sn bimetallic carrier and Ir. In addition, the Mn-Sn bimetallic carrier can reduce the oxygen adsorption energy on the catalyst surface. Therefore, the Mn-Sn bimetallic carrier helps to reduce the Ir loading and improve the OER activity and stability. The provided catalyst has a low overpotential for the acidic oxygen evolution reaction, high catalyst activity, and has broad application prospects in the field of acidic water electrolysis and oxygen evolution.
[0085] In some embodiments, in a proton exchange membrane water electrolysis reaction, the method for preparing an anode includes:
[0086] Dispersing the catalyst in the dispersion, mixing and pre-treating to obtain a slurry;
[0087] The slurry is sprayed on polytetrafluoroethylene to form an anode hydrogen evolution catalyst;
[0088] The anode hydrogen evolution catalyst is then transferred to the proton exchange membrane to obtain the anode.
[0089] The catalyst powder is dispersed in a dispersion of a perfluorosulfonic acid polymer solution (Nafion solution, including D520 or D2020), a n-propanol or isopropanol solution and ultrapure water. The water-to-alcohol ratio is 1:1. A typical ratio may be: 1 g catalyst, 0.1 g Nafion solution, 1 mL n-propanol or isopropanol, and 1 mL ultrapure water. The mixing uniformity treatment operation includes: using a cell disruptor to mix uniformly for 30 minutes to ensure that the catalyst particles are fully dispersed in the solution. Ball milling is performed to further improve the uniformity of the dispersion. Ultrasonic treatment is used again to ensure that there is no agglomeration. The uniform catalytic suspension is heated and stirred at 80°C to ensure the uniformity and stability of the solution.
[0090] Use a spray gun or other spraying equipment to spray the uniform catalytic suspension directly on the active area of 1cm 2 The catalyst loading was accurately determined by the change in the mass of PTFE before and after spraying.
[0091] Place the PTFE substrate sprayed with the catalyst and the commercial cathode Pt / C catalyst on a proton exchange membrane (such as Nafion membrane). Preheat in a hot press at 150°C for 5 minutes to ensure the initial bonding between the layers. Continue hot pressing for 5 minutes at a pressure of 1.5MPa to ensure a strong bond between the catalyst layer and the proton exchange membrane. During the hot pressing process, pay attention to maintaining a uniform distribution of pressure and temperature to avoid defects caused by local overheating or uneven pressure.
[0092] In some embodiments, the mass ratio of Nafion (ionomer) to catalyst in the slurry is 1:0.10-0.20. This ratio can affect the conductivity and stability of the catalyst layer. The solid content of the slurry is 0.5%-2%. This parameter can affect the viscosity and spraying effect of the slurry. A lower solid content can increase the fluidity of the slurry, but may cause the coating to be too thin; a higher solid content can increase the coating thickness, but may cause the slurry to be too viscous and difficult to spray. In some embodiments, a commercial cathode Pt / C catalyst and a sprayed anode catalyst are usually transferred to a proton exchange membrane together to form a membrane electrode.
[0093] Example
[0094] Example 1
[0095] This embodiment provides a composite material and a preparation method thereof, wherein the preparation method comprises the following steps:
[0096] S10, providing 2.8 mmol of KMnO4, 0.14 mmol of SnCl2·2H2O, 1 ml of HCl (mass fraction 37%), 0.2 g of IrCl3, and 0.16 g of sodium acetate;
[0097] S20, 2.8mmol KMnO4, 0.14mmol SnCl2·2H2O and 1ml HCl (mass fraction 37%) were dissolved in 40ml water and stirred for 30min to ensure full mixing; the mixed solution was placed in a 100ml polytetrafluoroethylene-lined autoclave and reacted under hydrothermal conditions at 140℃ for 12h. After the reaction was completed, it was cooled to room temperature. It was then washed with water several times, filtered, and vacuum dried at 40℃ to obtain Mn 0.86 Sn 0.14 O2 nanowires.
[0098] S30, the obtained Mn 0.86 Sn 0.14 0.05g of O2 nanowires and 0.16g of sodium acetate were dissolved in 50ml of ethanol, stirred for 30min to ensure uniform mixing, and the mixed solution was placed in a 100ml polytetrafluoroethylene-lined autoclave for 12h under hydrothermal conditions at 120℃. After the reaction was completed, it was cooled to room temperature. It was then washed with water several times, filtered, and vacuum dried at 40℃ to obtain IrO2-Mn 0.86 Sn 0.14 O2 composite material.
[0099] The carrier obtained in Example 1 was subjected to X-ray diffraction (XRD) and scanning electron microscopy (SEM), and the following Figure 1 The XRD patterns and Figure 2 As shown in the SEM figure, it can be seen that the structural formula of the carrier is Mn 0.86 Sn 0.14 O2, in which Sn is well doped into the manganese dioxide crystals.
[0100] Example 2
[0101] This example is basically the same as Example 1, except that the amount of SnCl2·2H2O used is 0.28 mmol. The Ir content in Example 2 is 38.8%.
[0102] The carrier obtained in Example 2 was subjected to X-ray diffraction (XRD) and scanning electron microscopy (SEM), and the following Figure 3 The XRD patterns and Figure 4 As shown in the SEM figure, it can be seen that the structural formula of the carrier is Mn 0.82 Sn 0.18 O2, in which Sn is well doped into the manganese dioxide crystals.
[0103] Example 3
[0104] This embodiment is basically the same as embodiment 1, except that the preparation of the carrier in step S21 is slightly different, including:
[0105] 0.49 g of manganese acetate tetrahydrate (245.09 gmol -1 ) was dissolved in 20 mL of water to obtain a first solution; 0.43 g of hot Na2SnO3 (212.69 gmol -1) was dissolved in 10 mL of water, and the solution became colorless after stirring to obtain a second solution; the second solution was slowly dripped into the first solution and stirred for 1 h, followed by adding 8 mL of aqueous ammonia and stirring again for 1 h.
[0106] The reason why the manganese precursor and the tin precursor are separately prepared into solutions and then mixed is that manganese acetate and sodium stannate will react. In order to obtain more uniform particles, they are separately prepared into solutions and slowly added dropwise. The final composite material is Ir-MnSn(OH)6, in which the Ir content is 23.39%.
[0107] The carrier obtained in Example 3 was subjected to X-ray diffraction and scanning electron microscopy, and the following Figure 5 The XRD patterns and Figure 6 As shown in the SEM image, it can be seen that the structural formula of the carrier is MnSn(OH)6.
[0108] Example 4
[0109] This embodiment is basically the same as embodiment 1, except that the amounts of the manganese precursor and the tin precursor are different, wherein the manganese precursor is 0.7 mmol KMnO4 and the tin precursor is 0.1 mmol SnCl2·2H2O.
[0110] The final composite material is IrO2-Mn 0.875 Sn 0.125 O2.
[0111] Comparative Example 1
[0112] Commercial iridium oxide was purchased as a catalyst.
[0113] Transmission electron microscopy (TEM) was performed on iridium oxide to obtain the following Figure 7 The TEM images shown in the figure and the particle size test results are as follows Figure 8 Particle size distribution diagram shown.
[0114] Comparative Example 2
[0115] Compared with Example 1, the difference is that no tin precursor is added. The composite material finally obtained is IrO2-MnO2.
[0116] The carrier obtained in Comparative Example 2 was subjected to X-ray diffraction to obtain the following Fig. 9 From the XRD pattern shown, it can be seen that the structural formula of the carrier is MnO2.
[0117] Comparative Example 3
[0118] Compared with Example 1, the difference is that no manganese precursor is added. The composite material finally obtained is IrO2-SnO2.
[0119] The carrier obtained in Comparative Example 3 was subjected to X-ray diffraction to obtain the following Fig.10 From the XRD pattern shown, it can be seen that the structural formula of the carrier is SnO2.
[0120] Application Examples and Comparative Examples
[0121] Application Example 1
[0122] The composite material (IrO2-Mn 0.86 Sn 0.14 O2) is used as OER, including:
[0123] First, the catalyst was dispersed in a mixture of Nafion solution, n-propanol or isopropanol solution and ultrapure water (where the water-to-alcohol ratio was 1:1), mixed evenly for 30 minutes using a cell disruptor, ball milled, and then ultrasonicated. At 80°C, the uniform catalytic suspension was directly sprayed on an active area of 1 cm 2 The catalyst loading was accurately determined by the mass change of PTFE before and after spraying. The sprayed anode catalyst and commercial cathode Pt / C catalyst were then transferred to the proton exchange membrane.
[0124] Performance test: In a three-electrode system, in an oxygen-saturated 0.5MH2SO4 solution, 10mA / cm 2 At this current density, the overpotential of the oxygen evolution reaction is only 246 mV. 2 It can be stable for 260h at the current density. As the anode of proton exchange membrane electrolysis water, at 1A*cm -2 At current density of 0.45mg*cm -2 At an iridium loading of 0.86 Sn 0.14 O2 can run stably for more than 3000h.
[0125] Application Example 2
[0126] The composite material (IrO2-Mn 0.82 Sn 0.18 O2) is used as OER.
[0127] Performance test: In a three-electrode system, in an oxygen-saturated 0.5MH2SO4 solution, 10mA / cm 2 At this current density, the overpotential of the oxygen evolution reaction is only 217 mV. 2It can be stable for 330h at a current density of 1A*cm -2 At current density of 0.45mg*cm -2 At an iridium loading of 0.82 Sn 0.18 O2 can run stably for more than 3600h.
[0128] Application Example 3
[0129] The composite material (Ir-MnSn(OH)6) obtained in Example 3 was used for OER.
[0130] Performance test: In a three-electrode system, in an oxygen-saturated 0.5MH2SO4 solution, 10mA / cm 2 At this current density, the overpotential of the oxygen evolution reaction is only 242 mV. 2 It can be stable for 240h at the current density. As the anode of proton exchange membrane electrolysis water, at 1A*cm -2 At current density of 0.3mg*cm -2 With an iridium loading of 1.54kcal, Ir-MnSn(OH)6 can operate stably for more than 4000h.
[0131] Application Example 4
[0132] The composite material (IrO2-Mn 0.125 Sn 0.875 O2) is used as OER.
[0133] Performance test: In a three-electrode system, in an oxygen-saturated 0.5MH2SO4 solution, 10mA / cm 2 At the current density of 10 mA / cm, the overpotential of oxygen evolution reaction is only 317 mV. 2 It can be stable for 30h at the current density. As the anode of proton exchange membrane electrolysis water, at 1A*cm -2 At current density of 0.5 mg*cm -2 At an iridium loading of 0.875 Sn 0.125 O2 can run stably for more than 1000h.
[0134] Application Comparative Example 1
[0135] IrO2 in Comparative Example 1 was used for OER.
[0136] Performance test: As anode for proton exchange membrane water electrolysis, at 1A*cm -2 At current density of 0.5 mg*cm -2At an iridium loading of 100%, IrO2 can operate stably for more than 110 hours. The disadvantages are that it is expensive, has low activity, and is not stable at low iridium loadings.
[0137] Application Comparative Example 2
[0138] The composite material (IrO2-MnO2) obtained in Comparative Example 2 was used for OER.
[0139] Performance test: In a three-electrode system, in an oxygen-saturated 0.5MH2SO4 solution, 10mA / cm 2 At this current density, the overpotential of the oxygen evolution reaction is only 274 mV. 2 It can be stable for 100h at the current density. As the anode of proton exchange membrane electrolysis water, at 1A*cm -2 At current density of 0.3mg*cm -2 At an iridium loading of 1.54 N·m2, IrO2-MnO2 can operate stably for more than 2000 h.
[0140] Application Comparative Example 3
[0141] The composite material (IrO2-SnO2) obtained in Comparative Example 3 was used for OER.
[0142] Performance test: In a three-electrode system, in an oxygen-saturated 0.5MH2SO4 solution, 10mA / cm 2 At this current density, the overpotential of the oxygen evolution reaction is only 315 mV. 2 It can be stable for 50h at the current density. As the anode of proton exchange membrane electrolysis water, at 1A*cm -2 At current density of 0.3mg*cm -2 At an iridium loading of 1.54 N·m, IrO2-SnnO2 can operate stably for more than 500 h.
[0143] In summary, the present application provides an Ir catalyst carrier loaded with a Mn-Sn bimetallic material. Among them, the manganese-tin carrier loading can reduce the amount of Ir used in the catalyst, thereby improving the atomic utilization efficiency of Ir. The MnO2 carrier has good stability in an acidic system, but its conductivity can be improved by doping Sn with high electronegativity and an outer electronic structure similar to that of carbon. The oxygen adsorption performance of IrO2 can be adjusted by carrier loading, so that the oxygen adsorption performance of the catalyst is moderate, thereby improving the activity and stability of OER. Among them, tin doping can improve the conductivity of the carrier, optimize the electronic structure of the catalyst, and keep iridium in a lower chemical state, improve the antioxidant capacity of iridium, thereby enhancing the stability of the catalyst in the OER reaction. The oxygen adsorption energy of the iridium-based catalyst can be adjusted by tin doping, so that the oxygen adsorption energy on the catalyst surface is moderate, thereby improving the OER activity and stability.
[0144] The method of the present invention has simple preparation process, low cost, easy control, and is suitable for batch preparation. The obtained catalyst has a low overpotential of the acidic oxygen evolution reaction, high catalyst activity, and has broad application prospects in the field of acidic water electrolysis oxygen evolution.
[0145] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0146] The above-described embodiments are only used to illustrate the technical solutions of the embodiments of the present application, rather than to limit them. Although the embodiments of the present application are described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the embodiments of the present application, and should all be included in the protection scope of the embodiments of the present application.
Claims
1. A composite material, characterized in that: A carrier comprising a metal compound doped with a metal and an iridium element or iridium oxide loaded on the surface of the carrier; The metal is selected from at least one of manganese and tin; The metal compound is selected from at least one of manganese dioxide, tin oxide, stannous hydroxide and tin hydroxide.
2. The composite material according to claim 1, characterized in that The molar ratio of manganese element to tin element in the carrier is 1:(0.1-5).
3. A method for preparing a composite material, characterized in that: The following steps are involved: Provide manganese precursor, tin precursor, reaction additives, iridium source and solvent; Mixing the manganese precursor, the tin precursor and the reaction additive, and reacting to obtain a carrier; The carrier, the iridium source and the solvent are mixed and reacted to obtain the composite material.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the carrier to the iridium source is 1:(0.25-4).
5. The preparation method according to claim 3, characterized in that: The manganese precursor includes at least one of manganese acetate, manganese chloride and potassium permanganate; And / or, the tin precursor includes at least one of tin chloride, stannous chloride and sodium stannate; And / or, the reaction additive includes at least one of hydrochloric acid, sulfuric acid, nitric acid, ammonia water and ethylenediamine.
6. The preparation method according to claim 3, characterized in that: The iridium source comprises at least one of iridium trichloride and chloroiridic acid; And / or, the solvent includes at least one of water, ethanol, n-propanol and isopropanol.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The step of mixing the manganese precursor, the tin precursor and the reaction additive to obtain a carrier comprises: At 100°C to 200°C, react for 6h to 18h and then cool to room temperature; washing and vacuum drying at 40°C to 60°C to obtain the carrier; And / or, the carrier, the iridium source and the solvent are mixed and reacted to obtain the composite material, comprising: At 100°C to 200°C, react for 6h to 18h and then cool to room temperature; The composite material is washed and vacuum dried at 40° C. to 60° C. to obtain the composite material.
8. A catalyst, characterized in that A composite material comprising the composite material according to claim 1 or 2 or a composite material prepared by the preparation method according to any one of claims 3 to 7.
9. A proton exchange membrane water electrolysis reaction, characterized in that: The catalyst according to claim 8 is used as the anode oxygen evolution catalyst.
10. The proton exchange membrane water electrolysis reaction according to claim 9, characterized in that: The method for preparing the anode comprises the following steps: Dispersing the catalyst in the dispersion, mixing and pre-treating to obtain a slurry; Spraying the slurry onto polytetrafluoroethylene to form the anode hydrogen evolution catalyst; Then, the anode hydrogen evolution catalyst is transferred to a proton exchange membrane to obtain the anode.